Melodic intonation therapy in a Polish-speaking adolescent with developmental language disorder: a clinical case report - Pastuszek-Lipińska, Barbara (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2025)
Specific language impairment (SLI), also referred to as developmental language disorder (DLD), affects approximately 7-10% of children worldwide. In Poland, approximately 300,000 children aged 4-14 are estimated to be affected. The aim of this case study was to evaluate the effectiveness of melodic intonation therapy (MIT) in a boy diagnosed with SLI/DLD. The case concerned a 16-year-old boy with SLI/DLD, who had not previously benefited from school-based speech therapy. A modified MIT programme was applied over 74 hours (3-5 sessions per week, 0.5-1 hour). Neuropsychological assessment was performed before and after intervention using the AFA Scale. Observable improvements in repetition, naming, conversation, picture description, and spontaneous speech were documented. Progress was confirmed both through structured assessment and clinical observation. Melodic intonation therapy appears to be a potentially valuable intervention for children with SLI/DLD. Controlled studies are warranted.